Laparoscopic splenectomy and azygoportal disconnection combining with pre- and postoperative endoscopic intervention - A sandwich-style sequential therapy for portal hypertensive bleeding: A retrospective cohort study - Ba, Dou-Sheng; Zhang, Chi; Jin, Sheng-Jie; Chen, Ping; Jiang, Guo-Qing (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: In patients who survive the first esophageal variceal bleeding (EVB) resulting from portal hypertension, the probability of fatal esophageal variceal re-bleeding (EVR) is high. We have developed a sandwich-style sequential therapy combining laparoscopic splenectomy and azygoportal disconnection (LSD) with preoperative and postoperative endoscopic intervention (LSDE). The aim of the present study was to investigate whether LSDE is safe and effective and to evaluate whether the postoperative EVR rate for LSDE was lower than that for LSD without periodical postoperative endoscopic intervention (NLSDE). Materials and Methods: We retrospectively investigated the outcomes of 226 patients with cirrhosis with EVB and secondary hypersplenism who all received preoperative endoscopic variceal ligation (EVL) to manage emergency EVB then underwent NLSDE (n=106) or LSDE (n=120) between February 2012 and April 2016. The perioperative and follow-up variables of the two groups were evaluated. Results: Between the two groups, there were no differences in number of blood transfusions, intraoperative blood loss, postoperative complications, and hospital stay. LSDE showed shorter operation time (p=0.001) and lower EVR rates during the periods ranging from 1 to 12 months, 4 to 6 months, 4 to 12 months, and 7 to 12 months (all p Conclusion: Laparoscopic splenectomy and azygoportal disconnection with periodical postoperative endoscopy is safe and effective for reducing the EVR rate in cirrhotic portal hypertension. Cite this article as: Ba DS, Zhang C, Jin SJ, Chen P, Jiang GQ. Laparoscopic splenectomy and azygoportal disconnection combining with pre- and postoperative endoscopic intervention - A sandwich-style sequential therapy for portal hypertensive bleeding: A retrospective cohort study. Turk J Gastroenterol 2018; 29: 669-75.